Cogging Torque Reduction in a 40-Pole/24-Slot Permanent Magnet Generator Using Magnet Edge Shaping and Slot Opening Adjustment - Irwan Firdaus; Dhami Johar Damiri; Tajuddin Nur (Green Publisher Indonesia, 2026)
Indonesia’s relatively low average wind speed (3–6 m/s) necessitates low-speed wind turbines using multipole permanent magnet generators (PMGs); however, the 40-pole/24-slot configuration tends to produce high cogging torque. This elevated cogging torque can negatively affect starting performance, induce vibration, and reduce overall efficiency. This study reduces the cogging torque of a 40-pole/24-slot PMG through magnet edge shaping and stator slot-opening adjustment. A 2D magnetostatic finite element analysis (FEA) was performed using FEMM 4.2 for three designs: a baseline model (2.0 mm slot opening), an edge-shaped model, and a combined edge-shaped model with a 1.8 mm slot opening. The maximum cogging torque decreased from 0.016676 N·m to 0.000395 N·m and 0.000141 N·m, corresponding to reductions of 97.63% and 99.15%, respectively. Flux density maps confirm a more uniform air-gap flux distribution in the combined design without altering the machine’s main dimensions. The combination of magnet edge shaping and slot-opening reduction is highly effective in minimizing cogging torque without changing the generator’s primary dimensions. This method is practical and suitable for improving the performance of small-scale PMGs in low-speed wind turbine applications.